Diguanylate cyclase Dgc1 synthesizes c-di-GMP and modulates WL gum exopolysaccharide production in Sphingomonas sp. WG - Hui Li; Yanhui Jia; Hangxu Liu; Zaimei Zhang; Mengqi Chen; Huiyu Zheng; Mengqing Xu; Mengmeng Zang; Dong Wang; Yawei Sun; Hu Zhu; Jiqian Wang (Bioresource Technology, 2026)

Aptamer/magnetic-MIP dual-recognition sandwich biosensor for rapid and recyclable determination of kanamycin in food - Tingting Wang; Fengjuan Zhao; Zhiguang Suo; Yong Liu; Yawei Huang; Min Wei (Analytica Chimica Acta, 2026)

Low-intensity electrical stimulation enhances phthalate ester biodegradation by activated sludge through real-time multi-scale regulation - Huabo Gong; Zhuo-Ning Xian; Jinwen Hu; Jinming Luo; Yawei Wang; Xiaowei Liu; Nanwen Zhu (Water Research, 2026)

Nitrogen-doped pyrite composite for enhanced Fe(III)/Fe(II) cycling and broad-spectrum pollutant degradation via peroxymonosulfate activation - Yan Yan; Zhenjie Li; Chunwei Liu; Yuan Qiao; Caiping Hu; Longquan Zhang; Xiaoguo Shi; Yizhe Zhao; Yawei Gu; Wenyu Wang (Process Safety and Environmental Protection, 2026)

Enhancing the flotation separation of lithium adsorbents via sodium oleate-induced hydrophobic modification: Hydrophobization mechanism and field validation - Yuanliang Yang; Gang Jin; Jianqiang Tao; Chang Liu; Yawei Han; Ruoyu Ding; Yaqi Yang; Xiaolong Xiao; Xiaobing Li (Journal of Water Process Engineering, 2026)

Structure-activity relationship and salinity-driven degradation pathway and toxicity divergence of bromophenols during advanced reduction in VUV/sulfite system - Yawei Shi; Keyan Liu; Yan Wang; Ya Sun; Zonglin Pan; Mengqi Li; Guanghui Ding (Journal of Water Process Engineering, 2026)

Structural changes of costameres and actomyosin induced by postmortem resonant stimulation - Wanhong He; Yingbo Peng; Haixia Huang; Hao Wen; Chuanfeng Liu; Zhenzhen Li; Yawei Zhang (Food Research International, 2026)

Urban–rural divergence of wintertime organic aerosol molecular fingerprints in PM2.5 revealed by FT–ICR MS - Shanshan Tang; Jintian Zhang; Yuansheng Wang; Jitao Lv; Lei Liu; Weijun Li; Yawei Wang (Atmospheric Environment, 2026)

The meteorological and anthropogenic drivers of O3 and PM2.5 pollution in China's Ningbo based on WRF-CMAQ-ISAM - YuZhan Xie; Tijian Wang; Pulong Chen; Kuanguang Zhu; Tao Niu; Rong Li; Mengmeng Li; Hao Wu; Yawei Qu; Xu Liu; Congwu Huang (Atmospheric Pollution Research, 2026)

Dynamic embeddedness within the structural connectome characterizes macroscale functional organization of the human brain - Weiyang Shi; Congying Chu; Wen Li; Lingzhong Fan; Siyang Li; Luqi Cheng; Ming Song; Haiyan Wang; Zhenwei Dong; Shiqi Di; Yuejia Zhong; Yawei Ma; et al. (Science Bulletin, 2026)

Experimental investigation of oxygen-enriched combustion in conjunction with plasma ignition and plasma-assisted combustion to improve ammonia combustion - Chen Wu; Qifu Lin; Dianwu Wu; Chengzhou Liu; Shilong Zhong; Hansheng Feng; Longwei Chen; Zhenyang Li; Yiman Jiang; Guangnan Luo; Yawei Song; Weiye Chen; et al. (Fuel, 2026)

N and S co-doped graphene-based single-atom catalysts for highly efficient nitrate reduction - Jin-Hang Liu; Yu Sun; Xiaoduo Jiang; Huixiong Jiang; Ruirui Wang; Yawei Wang; Huixian Ye; Xiudong Chen; Li-Ming Yang (Fuel, 2026)

A functional lactic acid bacteria strain that naturally produces hydroxytyrosol and its impact on the antioxidant activity and post-acidification of fermented milk - Panpan Han; Yangliu Liu; Min Zhang; Yinglin Chen; Simiao Zhai; Zhixin Wang; Yawei Ning; Yingmin Jia (Food Bioscience, 2026)

Local versus external dust source contributions to northern China and selected downwind cities: Evidence from representative dust events in 2025 - Yawei Fan; Heqiang Du; Shengfei Yang; Yongjie Liu; Changzhen Yan; Xiao Zheng (Environmental Pollution, 2026)

Constructing atomic-scale proton channels in polymeric carbon nitride via synergistic oxygen and carbon defects for efficient CO2 photoreduction - Ruirui Wang; Yiming Wang; Jinhang Liu; Huixiong Jiang; Ran Wang; Yang Wang; Shunhang Wei; Xiaoxiang Xu; Yawei Wang (Chemical Engineering Journal, 2026)

Dual-nitrogen coordination engineering enables porous carbon-confined Pt-FeN4 atomic interfaces for durable, low-Pt PEM fuel cells - Xiaoqian Xu; Nengneng Xu; Qin Cao; Yuheng Guo; Meng Li; Yuhao Liu; Yawei Li; Guicheng Liu; Woochul Yang; Jong Min Kim; Momo Safari; Jinli Qiao (Chemical Engineering Journal, 2026)

Enhanced net carbon dioxide sink in rice-duckweed system: Evidence from the diurnal flux variation - Weixuan Liu; Ning Gao; Yawei Li; Xiaoyin Liu; Xue Zhou; Yihao Peng; Lili Zhu; Jian Meng; Junzeng Xu (Agriculture, Ecosystems & Environment, 2026)

Corrigendum to “Long-term assessment of soil wind erosion and dust emissions in China from 2000 to 2023 using an improved erodibility factor” [Aeolian Res. 76 (2026) 101049] - Yawei Fan; Heqiang Du; Shengfei Yang; Yongjie Liu; Changzhen Yan; Xiao Zheng (Aeolian Research, 2026)

Rhizosphere reactive oxygen species as a protective barrier suppress Fusarium oxysporum invasion in tomato - Yaru Zhu; Huiqiang Yang; Siqi Shen; Meng Liu; Zelin Hao; Yawei Zhou; Jinbo Liu; Hanzhong Jia (Environmental Chemistry Letters, 2026)

Exposure to multiple metals, maternal glucose homeostasis and gestational diabetes mellitus: A prospective cohort study - Hui Guo; Sijia Liu; Wenjing Li; Yongliang Feng; Ping Zhang; Changqing Li; Shuqing Bai; Yuanyuan Yang; Xi Chen; Suping Wang; Yawei Zhang; Zhijun Meng; et al. (Environmental Research, 2026)

Melanocyte proliferation gene 1 regulated metabolic reprogramming in acute myocardial infarction based on the AMPK/mTOR pathway - Shihui Zhu; Tianyi Qu; Zheng Liu; Yawei Gao; Xiaoxia Chang; Hongqin Yu (Toxicology and Applied Pharmacology, 2026)

Sustainable lithium extraction from low-grade aqueous resources via reverse Li/Mg separation enabled by hydrated cation-π interaction - Huixiong Jiang; Xing Liu; Jin-Hang Liu; Xiudong Chen; Ruirui Wang; Yawei Wang; Changchao Zhan; Xiaohua Cao; Xiushen Ye; Guosheng Shi (Journal of Cleaner Production, 2026)

Efficient removal of N-nitrosodimethylamine and triclosan by nFe@Fe3O4 nanocomposites: Enhanced generation of active hydrogen atoms - Ying Han; Wanqing Zhao; Xiaoping Zheng; Chuwei Li; Lingyun Tang; Tengfei Zhang; Yawei Xie; Hongyuan Liu (Journal of Environmental Chemical Engineering, 2026)

Accelerated peroxymonosulfate activation via internal electron migration within Co3O4/Bi2Fe4O9 for efficient phenol degradation - Bo Liu; Hangyu Shi; Yawei Wang; Rui Liu; Shuangshuang Zuo; Qianqian Nie; Lei Yang; Hesheng Yu (Journal of Environmental Sciences, 2026)

Understanding the differences in ignition and combustion characteristics between raw coal and pyrolyzed char: A combined PLIF measurement and DFT calculation - Yawei Song; Sheng Su; Qifu Lin; Longwei Chen; Chengzhou Liu; Weiye Chen; Zhenyang Li; Yiman Jiang; Dianwu Wu; Hansheng Feng; Guangnan Luo; Jun Xiang (Fuel, 2026)

Long-term assessment of soil wind erosion and dust emissions in China from 2000 to 2023 using an improved erodibility factor - Yawei Fan; Heqiang Du; Shengfei Yang; Yongjie Liu; Changzhen Yan; Xiao Zheng (Aeolian Research, 2026)

Enhanced reduction of 3-chloronitrobenzene by sulfidated microscale zero-valent iron: Performance and mechanism in anaerobic and aerobic systems - Ying Han; Chuwei Li; Qingjie Lu; Xinhui Ye; Wanqing Zhao; Yawei Xie; Haijiao Xie; Hongyuan Liu (Process Safety and Environmental Protection, 2026)

LC-MS/MS analysis of polar pesticides in mango: enantiomers, docking, and retention mechanisms - Hao Yang; Yue Geng; Shu Lin; Yawei Xu; Lu Wang; Yi Peng; Yaping Xu; Xiaowei Liu; Zeying He (Food Chemistry, 2026)

Molecular dynamics simulation of polyamide based reverse osmosis for boron removal - Yawei Du; Mengru Cui; Jingxin Wei; Yanping Li; Yize Liu; Shizhao Wang; Zhiyong Ji (Desalination, 2026)

Transcriptome profiling of AP2/ERF family members and functional characterization of CaAP2/ERF99 in pepper defense against Phytophthora capsici - Jie Wang; Muhammad Azeem; Yawei Li; Beibei Gong; Xueqi Li; Li Liu; Guangqiang Wu; Moli Chu; Wei Cheng (Plant Science, 2026)

A methodical comparative analysis of the improved dechlorination of trichloroethylene (TCE) using C-, N-, and S-modified zero-valent iron (ZVI) - Xiang Luo; Hongwei Chen; Hongjian Shen; Ling Zhang; Jinbo Chen; Shuai Liu; Bo Gao; Honglei Zhang; Yawei Gu (Journal of Water Process Engineering, 2026)

Organic fractions in wastewater enabled simultaneous removal of NO3− and Cr(VI) under VUV185 irradiation - Yawei Xie; Shijie Wu; Xunfang Hu; Jinliang Wang; Dehua Ma; Wei Zheng; Rui Liu; Hongyuan Liu (Journal of Environmental Management, 2026)

Risk factors for antibiotic resistance and 30-day mortality among adult patients with acute leukemia and Escherichia coli bloodstream infection - Juan Wu; Wei Wang; Kaili Du; Zhongxian Liao; Yawei Shi; Munire Abudumaijiti; Jilai Liu; Jiadi Chen; Xinmiao Fu (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Parental HFPO-TA exposure induces intergenerational reproductive toxicity and DNA methylation alterations in zebrafish - Shasha Dong; Xiaohui Zhao; Xuan Ren; Jing Zhang; Zhibo Liu; Dan Yang; Ning Ji; Yawei Shi; Ya Sun; Guanghui Ding (ENGINEERING Environment, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Cathodic periodate activation driven by photocatalytic fuel cell for ciprofloxacin degradation - Yawei Xie; Shijie Wu; Yaozu Jin; Xunfang Hu; Jinliang Wang; Miaomiao Ye; Dehua Ma; Wei Zheng; Rui Liu; Hongyuan Liu (Journal of Water Process Engineering, 2026)

Microplastic-pathogen interactions differentially modulate tomato Fusarium wilt severity: The dependence of polymer biodegradability - Siqi Shen; Yawei Zhou; Ru Zhao; Meng Liu; Wenjiang Fu; Shuting Zhao; Chaokai Yan; Qi Gao; Dan Zhang; Yanhua Wang; Hanzhong Jia; Yahong Wei (Journal of Hazardous Materials, 2026)

Dual-pathway persulfate activation by mackinawite (FeS) for contaminant degradation: Overlooked role of Fe(IV) species and QSAR model - Bowen Yang; Zhihao Li; Yawei Liu; Qiang Ma; Dunqiu Wang; Longhui Zheng; Jiming Hao (Journal of Environmental Management, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Short-term effect of changing water regimes on the soil nematode community in rice-duckweed system under water-saving irrigation - Zeeshan Ahmed; Junzeng Xu; Weixuan Liu; Xiaoyin Liu; Yawei Li; Hang Guo; Shengyu Chen (European Journal of Soil Biology, 2026)

Applications of machine learning-based quantitative structure activity relationship (ML-QSAR) models in environmental science - Chao Chen; Yujia Tan; Yawei Liu; Miaomiao Sun; Zhiquan Wang; Xiangyong Zheng; Zhemin Shen; Min Zhao (Environmental Research, 2026)

Nutrient recovery from source-separated urine and urease inhibition during evaporation by a combination of salt, absorbent material, and dehumidification - Weikun Chen; Huijun Xiang; Chun Chen; Lanyue Feng; Ke Bei; Yawei Liu; Min Zhao; Xiangyong Zheng (Chemical Engineering Journal, 2026)

Machine learning reveals molecular substructure drivers of organic contaminant translocation in crops - Haodong Lang; Yang Cui; Wen Liu; Shanshan Tang; Wei Gao; Chengyu Zhai; Jing Lu; Yawei Wang (Science of The Total Environment, 2026)

Excellent infrared radiation performance and significant energy-saving efficiency of LaAlO3 ceramics via Ca2+/Co2+ co-doping - Qinghu Wang; Yangxi Liu; Guoping Wei; Liang Huang; Xueqing Wang; Shaobai Sang; Yibiao Xu; Xiong Liang; Yawei Li; Jiangtao Li; Olena Volkova; Emad M.M. Ewais; et al. (Chemical Engineering Journal, 2026)

An exergy-guided thermodynamic framework for the optimization of electro-membrane-based coupled process - Ruochen Shen; Yawei Du; Lurong Wang; Mengmeng Sun; Tianyi Chen; Shizhao Wang; Jingtao Bi; Wenhao Li; Jianlu Liu; Yingying Zhao (Water Research, 2026)

Brine-filled MXene “Sandwich” system for synergistically enhanced electrochemical energy storage and solar desalination - Bowen Liu; Xuedong He; Yawei Yang; Yuyao Shen; Yihong Liu; Qi Zhao; Xinye Xu; Mo Zhou; Tianyi Wang; Wenxiu Que (Chemical Engineering Journal, 2026)

Molecular-scale mechanism of extracellular protein over-flocculation for sewage sludge dewatering by polyacrylamide - Minmin Liu; Jiesi Zhang; Yawei Zhao; Wei Wang; Huihui Zhang; Wenzheng Yu (Water Research, 2025)

A multi-target QSAR model for simultaneously predicting the rate constants of reactions across multiple oxidation systems - Yawei Liu; Zhiquan Wang; Xiangyong Zheng; Min Zhao; Zhemin Shen (Journal of Hazardous Materials, 2025)

Involvement of two-component system CseB-C in differential regulation of rapamycin and elaiophylin biosynthesis in Streptomyces rapamycinicus - Yawei Zhao; Shangping Jin; Pan Wang; Yuan Wang; Na Liu; Aimei Liao; Zhe Sun; Yinhua Lu; Hailong Tian (Food Bioscience, 2025)

Lactobacillus rhamnosus GG-derived extracellular vesicles improve cholestatic liver injury by regulating the gut microbiota and bile acid metabolism - Zhongyu Wang; Yubo Wang; Yawei Qiu; Andrea Del Pilar Abreo Medina; Yongwang Liu; Mengdie Shi; Jinyan Li; Yanyan Wang; Xianjiao Liu; Xingxiang Chen; Kehe Huang; Yunhuan Liu (Chemical Engineering Journal, 2025)

A study on a correction method for channel wave energy consistency under geophone-bolt coupling - Guangzhong Ji; Lingyun Shi; Yawei Zhang; Shuai Xu; Keyue Liu (Acta Geophysica, 2025)

Rational design of an ultra-high-gain MoS2 phototransistor enabling room-temperature detection of few-photon signals and attomolar-level immunosensing - Zhengdao Xie; Yun Hui; Wenhua Zhou; Shengxuan Xia; Yawei Lv; Liwei Ouyang; Yang Chai; Xingqiang Liu; Bei Jiang; Chang Liu; Sen Zhang; Chenchen Chu; et al. (Science Bulletin, 2025)

Tuning electrode wettability to optimize nanobubble nucleation and reaction rates in water electrolysis - Zhenlei Wang; Yaxi Yu; Mengkai Qin; Hao Jiang; Zhenjiang Guo; Lu Bai; Limin Wang; Xiaochun Zhang; Xiangping Zhang; Yawei Liu (Chemical Engineering Journal, 2025)

Study on the NO2 pollution and its connection with PM2.5 and O3 in Dazhou based on source apportionment - Xu Liu; Pulong Chen; Congwu Huang; Tijian Wang; Tao Niu; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu (Atmospheric Pollution Research, 2025)

Dual roles of N6-methyladenosine in R-loop regulation of gene transcription and genome stability - Fangle Li; Feifan Zhang; Jie Li; Yu Zhang; Wenxuan Gong; Yawei Zhang; Mengxia Liu; Jie Ren; Dali Han (Science China Life Sciences, 2025)

A hybrid approach for optimizing soil greenhouse gas flux predictions: integrating machine learning outputs into hyperparameter-tuned regression trees - Mostafa RASTGOU; Shangkun LIU; Jin WANG; Yawei LI; Junzeng XU; Yong HE; Qianjing JIANG (Pedosphere, 2025)

Flexible erythritol-based spatiotemporal phase change films with multiple energy responses for wearable thermal management - Huimin Yan; Yan Kou; Shihui Zhang; Hanqing Liu; Nan Yin; Yawei Xu; Quan Shi (Chemical Engineering Journal, 2025)

The impact of the COVID-19 epidemic on anthropogenic emissions in the Beijing-Tianjin-Hebei region of China based on 3DVar sectoral emission inversion - Congwu Huang; Tao Niu; Tijian Wang; Mengmeng Li; Rong Li; Chaoqun Ma; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu; Yuzhan Xie (Journal of Hazardous Materials, 2025)

Radical and non-radical peroxymonosulfate activation induced by a novel ferromagnetic Fe1-xS/lignin-based biochar nanocomposite: Multi-pathway synergistic effects for bisphenol A removal - Minglu Zhang; Zunqing Wen; Longquan Zhang; Qingyun Wang; Lihua Zang; Qing Feng; Yawei Gu; Wenyu Wang; Ke Ma; Hao Zhang; Dandan Ji; Jun Liu; et al. (Chemical Engineering Journal, 2025)

MnFe2O4 coupled with MgAl-LDH for activation of periodate towards enhanced degradation of organic pollutants in water - Ya Sun; Chang Ma; Yawei Shi; Zonglin Pan; Yumei Xing; Yan Wang; Keyan Liu; Guanghui Ding (Journal of Water Process Engineering, 2025)

Pt-CeO2/SDB ternary structure achieved by modulating electronic interaction for high-efficiency toluene oxidation - Zun Liu; Guotan Liu; Xuanye Liu; Weihong Gao; Yudong Fu; Bin Sun; Yawei Shao; Guojun Dong (Journal of Environmental Chemical Engineering, 2025)

Energy-force coupling in interfacial solar vapor generation: A pathway to sustainable salt management - Yihong Liu; Yawei Yang; Bowen Liu; Qi Zhao; Yuyao Shen; Mengyuan Qiang; Yong Ma; Wenxiu Que (Desalination, 2025)

Excellent lithium storage performance of SnOx/Ti3C2 with low Sn content by controlling the oxygen vacancy content - Tingting Xu; Yawei Li; Jinghan Zhang; Haixiang Huang; Bogu Liu; Xiaohong Chen; Hong Zeng; Ying Wu (Chemical Engineering Journal, 2025)

Salidroside alleviates cardiomyocyte senescence by activating the AMPK-mediated signaling pathway - Lan Zhang; Yawei Liu; Zhijuan Hua; Yan Qin; Tao Wang; Na Li; Lei Song (Journal of Molecular Histology, 2025)

Methanol-driven advanced reduction of nitrate and 2,4,6-tribromophenol by UV-activated photolysis - Yawei Xie; Yue Wang; Shijie Wu; Hmuu Khet Nwe Zaw; Yaozu Jin; Shiyi Ni; Lyujun Chen; Hongyuan Liu (Process Safety and Environmental Protection, 2025)

The inhibition potentiality of sodium carboxymethyl cellulose on PhIP, Harman, and Norharman formation of fried beef patties at low NaCl level - Yi Zhao; Pinghua Deng; Ruoxi Ma; Shuang Teng; Hang Lu; Zheng Liu; Haotian Yu; Yawei Zhang (Meat Science, 2025)

Improved degradable, mechanical, and osteoimmunity-regulating performances of additively manufactured Zn-Mg alloy with heterogeneous microstructure for augmented bone regeneration - Zhengjun Lin; Luxin Liang; Yawei Li; Yanlin Wu; Jing Li; Bing Wang; Chao Chen; Tang Liu (Chemical Engineering Journal, 2025)

Gram-scale synthesis of unsupported Pt-rare earth nanosponge for enhanced stability in proton exchange membrane fuel cells - Chenhao Li; Hao Wang; Fangren Qian; Yawei Li; Qinqin Sang; Qingjun Chen; Jialiang Liao; Yihan Zhu; Yanrong Liu; Suojiang Zhang (Chemical Engineering Journal, 2025)

Quaternary ammonium COF-based proton exchange membranes for enhanced electrochemical hydrogen compression - Xiao Pang; Ziwen Liu; Shuting Xu; Kexin Lv; Benbing Shi; Xu Dong; Na Xing; Zhong Gao; Shiyi Zhu; Leilang Zhang; Zengguang Yao; Lijuan Cheng; et al. (Chemical Engineering Journal, 2025)

Experimental study on the failure mechanism of interbedded anti-dip rock slope induced by underground mining - Nanyun Wang; Zuliang Zhong; Yawei Xu; Xinrong Liu; Kaixin Zhu (Journal of Mountain Science, 2025)

Sustainable Ca(OH)2 deacidifiers derived from waste eggshells for free fatty acids removal: characterization, performance and thermodynamics - Yawei Wang; Chao He; Gang Li; Xinxin Liu; Liang Liu; Youzhou Jiao (Environment, Development and Sustainability, 2025)

Seasonal variation in two culture systems and genome-wide association analysis of taurine content in the foot muscles of the Pacific abalone (Haliotis discus hannai) - Ziheng Yin; Junyu Liu; Wenchao Yu; Yawei Shen; Yang Gan; Yexin Chen; Jinwei Ke; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2025)

Sufficient burial depth is a prerequisite for Chinese cyclina (Cyclina sinensis) to maintain normal life activities - Yurou Ma; Shiyu Yan; Zhengyu Shao; Guolong Zhou; Ang Hu; Yawei Bu; Huimin Wang; Xinqi Lv; Jianyu Liu; Yihua Chen; Zhiguo Dong (Aquaculture, 2025)

Removal of adsorbable organic halogens generated during advanced oxidation processes using UV/sulfite - Yawei Xie; Yue Wang; Mingdi Yang; Shijie Wu; Yaozu Jin; Rui Liu; Hongyuan Liu (Journal of Water Process Engineering, 2025)

Synergy of bismuth and tungsten in Bi2WO6 for PMS activation to enhance degradation of ammonium dibutyl dithiophosphate in flotation wastewater - Mingwei Shen; Teng Wang; Yawei Wang; Zhiyuan Li; Jiayou Liu; Ke Jin; Hesheng Yu (Journal of Water Process Engineering, 2025)

Ceramic ultrafiltration membrane as pretreatment for drinking water nanofiltration treatment: Performance, cleaning, and costs based on an engineering case - Yawei Xie; Chengyue Fan; Yichen Fang; Xiwang Zhu; Jiaming Yan; Haodong Liu; Hongyuan Liu (Journal of Cleaner Production, 2025)

Influence of alternate wetting and drying and duckweed on zooplankton abundance in rice paddy ecosystem - Zeeshan Ahmed; Weixuan Liu; Junzeng Xu; Yawei Li; Zahid Majeed (Journal of Environmental Management, 2025)

Mechanisms of antifungal activity of ehimensin F6 produced by Paenibacillus ehimensis HD against Penicillium expansum - Yuqing Huang; Dandan Liu; Yahui Liu; Ziwei Jia; Tengteng Zhao; Zhen Zhao; Yawei Ning; Xiaohui Liang; Zhixin Wang (International Journal of Food Microbiology, 2025)

A novel N/C co-modified FeS2 nanocomposite synthesized by wet-mechanochemical method for efficient peroxymonosulfate activation and nearly 100% SO4•─ selective generation - Longquan Zhang; Guangfei Gao; Xiaoguo Shi; Zunqing Wen; Minglu Zhang; Qingyun Wang; Qing Feng; Jing Sun; Xuezheng Liu; Ying Zhao; Yawei Gu; Wenqiang Jiang (Chemical Engineering Journal, 2025)

Proteomic insights from extracellular vesicles into the molecular mechanisms of health effects induced by Per- and polyfluoroalkyl substances - Yanping Li; Yadan Luo; Yang Liu; Na Li; Kai Huang; Lingxiangyu Li; Zhigang Li; Chao Han; Nali Zhu; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2025)

Revealing global supply risk of critical minerals essential for low-carbon energy technologies - Xinran Xing; Yawei Huang; Yao Wang; Heming Wang; Peng Wang; Tao Dai; Gang Liu; Asaf Tzachor (Journal of Cleaner Production, 2025)

Theoretical calculation on degradation mechanism of novel copolyesters under CALB enzyme - Yuanyang Ren; Zhiwen Cheng; Luwei Cheng; Yawei Liu; Mingyue Li; Tao Yuan; Zhemin Shen (Journal of Environmental Sciences, 2025)

Olanzapine exposure disordered lipid metabolism, gut microbiota and behavior in zebrafish (Danio rerio) - Yawei Wang; Fu You; Zhenyi Huang; Yuan Liu; Boya Yang; Xulu Chang; Guokun Yang; Xue Tian; Shikun Feng; Xiaolin Meng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Wood-derived closed pore hard carbon encapsulated micro-sized silicon anode design for long-term practical lithium-ion battery - Yingzhe Gao; Kai Zhang; Xiaohang Du; Guihua Liu; Yawei Du; Jingde Li (Chemical Engineering Journal, 2025)

Advances in regional-scale crop growth and associated process modeling - Wenfeng Liu; Yawei Bai; Taisheng Du; Mengxue Li; Hong Yang; Shichao Chen; Chuanbin Liang; Shaozhong Kang (Science China Earth Sciences, 2025)

Impact of surface reservoir construction on groundwater circulation and recharge in the Yangzhuang karst groundwater system, China - Yawei Feng; Fengxin Kang; Bintao Liu; Lichuan Zhang; Zhifeng Li; Xuetao Xing; Qingcheng He (Hydrogeology Journal, 2025)

Titanium-based hollow fiber membrane: Fabrication, optimization, and electrochemical filtration treatment performance - Xiaoqing Yan; Zonglin Pan; Xinyuan Zhou; Shuo Liu; Hang Yu; Ruisong Xu; Yawei Shi; Xinfei Fan; Tianjun Sun; Yongxin Song; Chengwen Song (Journal of Environmental Chemical Engineering, 2025)

Lovastatin enhances humoral and cellular immune responses to H1N1 influenza vaccine - Zuchen Song; Yantong Zhou; Lina Jiao; Tianyu Zhu; Ruihong Yu; Zheng Wang; Yawei Qiu; Jinfeng Miao; Ting Cai; Shun Zhang; Huina Liu; Haifeng Sun; et al. (Veterinary Microbiology, 2025)

A comprehensive screening method of oxidation systems based on reaction rate constant (k value) and emergy (Em value) - Yawei Liu; Zhiquan Wang; Zhiwen Cheng; Yuanyang Ren; Yujia Tan; Tao Yuan; Zhemin Shen (Science of The Total Environment, 2025)

A hybrid TCN-BiLSTM short-term load forecasting model for ship electric propulsion systems combined with multi-step feature processing - Shuo Pang; Liang Zou; Li Zhang; Hui Wang; Yawei Wang; Xingdou Liu; Jundao Jiang (Ocean Engineering, 2025)

The weak association between hypoxia tolerance and thermal tolerance increases the susceptibility of abalone to climate change - Yawei Shen; Yue Dai; Feng Yu; Wenzhu Peng; Junyu Liu; Weiwei You; Xuan Luo; Caihuan Ke; Nan Chen (Environmental Research, 2025)

Effects of traffic noise on the psychophysiological responses of college students: An EEG study - Nan Zhang; Chao Liu; Menglin Zhang; Yawei Guan; Wenhua Wang; Zihao Liu; Weijun Gao (Building and Environment, 2025)

Genetic dissection of a major locus SC9.1 conferring seed color in broomcorn millet (Panicum miliaceum) - Tianpeng Liu; Kongjun Dong; Jihong He; Mei Wang; Ruiyu Ren; Lei Zhang; Yawei Li; Minxuan Liu; Tianyu Yang (Theoretical and Applied Genetics, 2025)

Duckweed (Lemna minor L.) as a natural-based solution completely offsets the increase in ammonia volatilization induced by soil drying and wetting cycles in irrigated paddies - Weixuan Liu; Junzeng Xu; Yawei Li; Xiaoyin Liu; Xue Zhou; Yihao Peng; Yixuan Jia; Jian Gao; Qianjing Jiang; Yong He (Science of The Total Environment, 2024)

Evolution of hydrochemistry and water quality of karst groundwater under the effects of intense anthropogenic activities - Yawei Feng; Fengxin Kang; Yongli Guo; Zhifeng Li; Bintao Liu; Hongzhi Bu; Chunying Xia; Qingcheng He (Journal of Environmental Management, 2024)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

3DVar sectoral emission inversion based on source apportionment and machine learning - Congwu Huang; Tao Niu; Tijian Wang; Chaoqun Ma; Mengmeng Li; Rong Li; Hao Wu; Yawei Qu; Hongli Liu; Xu Liu (Environmental Pollution, 2024)

Versatile plant genome engineering using anti-CRISPR-Cas12a systems - Yao He; Shishi Liu; Long Chen; Dongkai Pu; Zhaohui Zhong; Tang Xu; Qiurong Ren; Chuan Dong; Yawei Wang; Danning Wang; Xuelian Zheng; Fengbiao Guo; et al. (Science China Life Sciences, 2024)

Molecular identification and expression patterns of sweet cherry HIPPs and functional analysis of PavHIPP16 in cold stress - Runrun Yu; Qiandong Hou; Hong Deng; Ling Xiao; Ke Liu; Yawei Wu; Guang Qiao (Planta, 2024)

Further geochronological constraints on the Xiuyan impact crater in northeast China - Zeyang Zhu; Chang Huang; Jing Wu; Yawei Li; Zhihao Sun; Min Zhang; Bin Zhang; Sheng-Hua Li; Jiaqi Liu (Frontiers of Earth Science, 2024)

Construction method and case study of digital twin system for combine harvester - Yanxin Yin; Bowen Ma; Zhijun Meng; Liping Chen; Mengnan Liu; Yawei Zhang; Bin Zhang; Changkai Wen (Computers and Electronics in Agriculture, 2024)

The effect of anthropogenic activities on the behavior of novel brominated flame retardants in surface soil of Northern China urbanized zone - Ziyan Liu; Yaqi Zhang; Feifei Li; Huifang Zhong; Runzeng Liu; Qiu Zhang; Rongguang Shi; Yingjun Wang; Yawei Wang (Science of The Total Environment, 2024)

Microstructural evolution and mechanics behavior of postmortem meat subjected to resonance - Yingbo Peng; Shujie Liu; Wanhong He; Boqun Liao; Yawei Zhang (Journal of Food Engineering, 2024)

Meta-analysis of GHG emissions stimulated by crop residue return in paddy fields: Strategies for mitigation - Qianying Wu; Ruitao Lou; Yong He; Yawei Li; Zhiming Qi; Junzeng Xu; Ji Liu; Mostafa Rastgou; Qianjing Jiang (Journal of Environmental Management, 2024)

Short time-series expression transcriptome data reveal the gene expression patterns and potential biomarkers of blood infection with LPS and poly (I:C) in Mandarin fish (Siniperca chuatsi) - Yawei Shen; Rahma Sakina Said Aly; Tiantian Chen; Hewei Jiang; Yufei Liu; Yongxiang Wang; Xiaowu Chen (Fish & Shellfish Immunology, 2024)

A high throughput method to assess the hypoxia tolerance of abalone based on adhesion duration - Yue Dai; Yawei Shen; Yanbo Liu; Weiwei Xia; Jiawei Hong; Yang Gan; Jie Huang; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2024)

Effects of basic amino acids on heterocyclic amines and quality characteristics of fried beef patties at low NaCl level - Pinghua Deng; Shuang Teng; Yu Zhou; Yuling Liu; Boqun Liao; Xiaopu Ren; Yawei Zhang (Meat Science, 2024)

A coupled STIRPAT-SD model method for land-use carbon emission prediction and scenario simulation at the county level - Hongjiang Liu; Wenchao Yin; Fengying Yan; Weiguang Cai; Yawei Du; Yuting Wu (Environmental Impact Assessment Review, 2024)

Hollow engineering of Co/N-doped C@carbon aerogel with hierarchical structure boosting interfacial polarization for ultra-thin microwave absorption and thermal insulation - Panpan Zhou; Shiyu Zhang; Wei Zhou; Chencheng Sun; Chengyao Hu; Shilin Yuan; Jiarui Li; Chang Liu; Yuchen Zhao; Yawei Kuang; Shuchang Wang; Qitu Zhang; et al. (Chemical Engineering Journal, 2024)

Alternating wet and dry irrigation cycles enhance the nitrogen “cache” function of duckweed in a rice-duckweed system - Weixuan Liu; Junzeng Xu; Yawei Li; Xiaoyin Liu; Ning Gao; Zeeshan Ahmed; Yihao Peng; Hao Liang; Qianjing Jiang; Yong He (Agriculture, Ecosystems & Environment, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

The application of chitosan quaternary ammonium salt to replace polymeric aluminum ferric chloride for sewage sludge dewatering - Minmin Liu; Sajid Rashid; Wei Wang; Huihui Zhang; Yawei Zhao; Xingmin Fu; Zhaoyang Su; Nigel Graham; Wenzheng Yu (Water Research, 2024)

Long‒term trends in surface thermal environment and its potential drivers along the urban development gradients in rapidly urbanizing regions of China - Chengyu Zhao; Hongkai Zhu; Shuyi Zhang; Ziwen Jin; Yiwen Zhang; Yawei Wang; Yadie Shi; Jianhui Jiang; Xiaoyong Chen; Min Liu (Sustainable Cities and Society, 2024)

Hydrothermal liquefaction of pig carcasses to biofuel: A techno-economic analysis - Youzhou Jiao; Chao Chang; Gaojie Xu; Chao He; Xinxin Liu; Gang Li; Yawei Wang; Xiaohui Pan; Guizhuan Xu; Qibin Li; Liang Liu (Process Safety and Environmental Protection, 2024)

TREM2 Deficiency Aggravates NLRP3 Inflammasome Activation and Pyroptosis in MPTP-Induced Parkinson’s Disease Mice and LPS-Induced BV2 Cells - Peiting Huang; Zhanyu Zhang; Piao Zhang; Jiezhu Feng; Jianwei Xie; Yinjuan Zheng; Xiaomei Liang; Baoyu Zhu; Zhenzhen Chen; Shujun Feng; Lijuan Wang; Jiahong Lu; et al. (Molecular Neurobiology, 2024)
Microglia-mediated neuroinflammation plays a crucial role in the pathogenesis of Parkinson’s disease (PD). Triggering receptor expressed on myeloid cells 2 (TREM2) confers strong neuroprotective effects in PD by regulating the phenotype of microglia. Recent studies suggest that TREM2 regulates high glucose-induced microglial inflammation through the NLRP3 signaling pathway. This study aimed to investigate the effect of TREM2 on NLRP3 inflammasome activation and neuroinflammation in PD. Mice were injected with AAV-TREM2-shRNA into both sides of the substantia nigra using a stereotactic injection method, followed by intraperitoneal injection of MPTP to establish chronic PD mouse model. Behavioral assessments including the pole test and rotarod test were conducted to evaluate the effects of TREM2 deficiency on MPTP-induced motor dysfunction. Immunohistochemistry of TREM2 and tyrosine hydroxylase (TH), immunohistochemistry and immunofluorescence Iba1, Western blot of NLRP3 inflammasome and its downstream inflammatory factors IL-1β and IL-18, and the key pyroptosis factors GSDMD and GSDMD-N were performed to explore the effect of TREM2 on NLRP3 inflammasome and neuroinflammation. In an in vitro experiment, lentivirus was used to interfere with the expression of TREM2 in BV2 microglia, and then lipopolysaccharide (LPS) and adenopterin nucleoside triphosphate (ATP) were used to stimulate inflammation to construct a cellular inflammation model. The expression differences of NLRP3 inflammasome and its components were detected by qPCR and Western blot. In vivo, TREM2 knockdown aggravated the loss of dopaminergic neuron and the decline of motor function. After TREM2 knockdown, the number of activated microglia was significantly increased, and the expression of cleaved caspase-1, NLRP3 inflammasome, IL-1β, GSDMD, and GSDMD-N was increased. In vitro, TREM2 knockdown aggravated the inflammatory response of BV2 cells stimulated by LPS and promoted the activation of NLRP3 inflammasome through the NF-κB pathway. In addition, TREM2 knockdown also promoted the expression of TLR4/MyD88, an upstream factor of the NF-κB pathway. Our vivo and vitro data showed that TREM2 knockdown promoted NLRP3 inflammasome activation and downstream inflammatory response, promoted pyroptosis, and aggravated dopaminergic neuron loss. TREM2 acts as an anti-inflammatory in PD through the TLR4/MyD88/NF-κB pathway, which extends previous findings and supports the notion that TREM2 ameliorates neuroinflammation in PD.

Pollution levels and probability risk assessment of potential toxic elements in soil of Pb–Zn smelting areas - Mingyue Li; Jinyang Zhou; Zhiwen Cheng; Yuanyang Ren; Yawei Liu; Linling Wang; Liu Cao; Zhemin Shen (Environmental Geochemistry and Health, 2024)

Exquisite visualization of mitophagy and monitoring the increase of lysosomal micro-viscosity in mitophagy with an unusual pH-independent lysosomal rotor - Rui Yang; Wei He; Changxin Zhu; Xifeng Yang; Yawei Kuang; Tao Zhu; Jingyang Xu; Yuang Zhao; Tingwang Jiang; Yushen Liu; Mengmeng Wei (Analytica Chimica Acta, 2024)

Sustainability evaluation of urban large-scale infrastructure construction based on dynamic fuzzy cognitive map - Hongyu Chen; Shidong Cheng; Yawei Qin; Wen Xu; Yang Liu (Journal of Cleaner Production, 2024)

Improved yield by optimizing carbon, nitrogen metabolism and hormone balance in apical kernels under low nitrogen conditions using the low nitrogen–tolerant maize variety - Qinlin Liu; Xinglong Wang; Yawei Wu; Tianqiong Lan; Fan Liu; Gui Wei; Chengcheng Lv; Fanlei Kong; Jichao Yuan (Field Crops Research, 2024)

Surface addition of Ag on PbO2 to enable efficient oxygen evolution reaction in pH-neutral media - Siming Li; Meng Shi; Chunxia Wu; Kaiqi Nie; Zheng Wei; Xiaopeng Jiang; Xinbing Liu; Huili Chen; Xinlong Tian; Daoxiong Wu; Yawei Li (Chemical Engineering Journal, 2024)

Surviving punishment by body reduction in a hierarchical society: A bioarcheological study of two punitive amputation cases in Eastern Zhou Dynasty (771–256 BCE) with references to the penal and medical systems of ancient China - Yawei Zhou; Yanmei Liu; Fei Yan; Qian Wang (Archaeological and Anthropological Sciences, 2024)

New insights into dust emission mechanism in natural environments based on a series of field observations - Heqiang Du; Xinlei Liu; Ruiqiang Ding; Yawei Fan; Xiufan Liu (Science of The Total Environment, 2024)

Elucidating drivers of severe wintertime fine particulate matter pollution episodes in the Yangtze River Delta region of eastern China - Lei Shu; Tijian Wang; Jane Liu; Zhixiong Chen; Hao Wu; Yawei Qu; Mengmeng Li; Min Xie (Science of The Total Environment, 2024)

Performance and membrane fouling characteristics of a drinking water multistage NF system based on membrane autopsy from a full-scale system - Chengyue Fan; Jiaming Yan; Haodong Liu; Yawei Xie; Hongyuan Liu (Journal of Water Process Engineering, 2024)

Comparative transcriptome analysis and genetic dissection of vegetative branching traits in foxtail millet (Setaria italica) - Tianpeng Liu; Xueying Liu; Jihong He; Kongjun Dong; Lei Zhang; Yawei Li; Ruiyu Ren; Tianyu Yang (Theoretical and Applied Genetics, 2024)

Boron promoted Fe3+/peracetic acid process for sulfamethazine degradation: Efficiency, role of boron, and identification of the reactive species - Yanhong Zhang; Guangbing Liu; Yuzhu Xue; Lichun Fu; Yawei Qian; Minhui Hou; Xiang Li; Chen Ling; Ying Zhang; Yuwei Pan (Journal of Environmental Sciences, 2024)

Production and utilization of the Chlorella vulgaris microalgae biochar as the fuel pellets combined with mixed biomass - Haiying Lu; Yawei Liu; Arunachalam Chinnathambi; Hesham S. Almoallim; G.K. Jhanani; Kathirvel Brindhadevi; P. Boomadevi; Changlei Xia (Fuel, 2024)

New insights into micro-algal astaxanthin's effect on deoxynivalenol-induced spleen lymphocytes pyroptosis in Cyprinus carpio: Involving mitophagy and mtROS-NF-κB-dependent NLRP3 inflammasome - Lei Diao; Wenjie Liu; Yawei Xu; Bin Zhang; Lingnan Meng; Rui Yin; Huijie Chen (Fish & Shellfish Immunology, 2024)

Mesopore-enhanced graphene electrodes with modified hydrophilicity for ultrahigh capacitive deionization - Ting Yang; Hongmei Zhang; Linpei Guo; Jing Wang; Zhiyuan Guo; Yawei Du; Jie Liu; Yingying Zhao; Panpan Zhang; Zhi-Yong Ji (Desalination, 2023)

Impacts of exposure to nanopolystyrene and/or chrysene at ambient concentrations on neurotoxicity in Siniperca chuatsi - Tiantian Chen; Hewei Jiang; Yawei Shen; Tingwen Cui; Zonglin Yang; Yufei Liu; Jinliang Zhao; Xiaowu Chen (Chemosphere, 2023)

Development of near-infrared reflectance spectroscopy (NIRS) model and genome-wide association study for glycogen and protein content in Pacific abalone - Junyu Liu; Muzhi Zhou; Ziheng Yin; Dan Huang; Liyan Zhu; Weiguang Zou; Wenchao Yu; Yawei Shen; Zekun Huang; Weiwei You; Caihuan Ke; Xuan Luo (Aquaculture, 2023)

Research on the risk evaluation of urban wastewater treatment projects based on an improved fuzzy cognitive map - Hongyu Chen; Jingyi Wang; Zongbao Feng; Yang Liu; Wen Xu; Yawei Qin (Sustainable Cities and Society, 2023)

Machine learning models based on residue interaction network for ABCG2 transportable compounds recognition - Ruining Guan; Wencheng Liu; Ningqi Li; Zeyang Cui; Ruitong Cai; Yawei Wang; Chunyan Zhao (Environmental Pollution, 2023)

Enhanced nitrate removal by alcohol-involved nitrate photolysis-induced advanced reduction process - Yawei Xie; Shiyi Ni; Shiming Wang; Chenda Wu; Keqi Huang; Dehua Ma; Lujun Chen; Rui Liu; Hongyuan Liu (Chemical Engineering Journal, 2023)

Identification of lower brominated bisphenol A analogs as the photooxidation products of tetrabromobisphenol A bis(2,3-dibromopropyl) ether (TBBPA-BDBPE) - Yuqing Jiang; Ling Wang; Minggang Zheng; Yongfeng Lin; Aifeng Liu; Yawei Wang; Ying Li (Science of The Total Environment, 2023)

Monitor water quality through retrieving water quality parameters from hyperspectral images using graph convolution network with superposition of multi-point effect: A case study in Maozhou River - Yishan Zhang; Xin Kong; Licui Deng; Yawei Liu (Journal of Environmental Management, 2023)

SIRT1 regulates osteoblast senescence through SOD2 acetylation and mitochondrial dysfunction in the progression of Osteoporosis caused by Cadmium exposure - Dehui Zhou; Yawei Ran; Rui Yu; Gang Liu; Di Ran; Zongping Liu (Chemico-Biological Interactions, 2023)

Identification of natural and anthropogenic sources and the effects of climatic fluctuations and land use changes on dust emissions variations in the Qinghai-Tibetan Plateau - Heqiang Du; Yawei Fan; Lihui Luo; Jie Liao; Zongxing Li; Xiufan Liu; Xinlei Liu; Xian Xue; Tao Wang (Agricultural and Forest Meteorology, 2023)

Impact of pyraclostrobin on the growth of Fusarium pseudograminearum and its control efficacy against wheat crown rot in Henan Province, China - Ying Hou; Yawei Chen; Lili Wang; Yiheng Zheng; Shengming Liu; Jianqiang Xu (Journal of Plant Pathology, 2023)

Examining the impacts of implicit economic policy on urban environmental pollution: Unveiling pathways for sustainable recovery - Ya Yang; Mengru Zhou; Yawei Hou; Run Tang; Bo Liu; Yue Deng (Resources Policy, 2023)

Nrf2 protects against renal fibrosis induced by chronic cadmium exposure in mice - Chengjie Chen; Zhengsheng Zhou; Siqi Yu; Yawei Ma; Gang Wang; Xue Han; Congcong Jiao; Junjun Luan; Zhiyuan Liu; Yuanyuan Xu; Huihui Wang; Qiang Zhang; et al. (Food and Chemical Toxicology, 2023)

Efficient anti-frosting on discrete nanoclusters via spatiotemporal control of condensation frosting dynamics - Siyan Yang; Yushan Ying; Wanbo Li; Yawei Feng; Rongfu Wen; Qixun Li; Yuanbo Liu; Bingang Du; Zuankai Wang; Xuehu Ma (Chemical Engineering Journal, 2023)

Reinforcing supramolecular hyaluronan hydrogels via kinetically interlocking multiple-units strategy - Ruofan Chen; Yujie Li; Yu Jin; Yawei Sun; Zhiyong Zhao; Yun Xu; Jiang-Fei Xu; Yuanchen Dong; Dongsheng Liu (Carbohydrate Polymers, 2023)

Community Characteristics of Soil Ectomycorrhizal Fungi under Different Forests in the Sandy Areas of Northeastern China - Jiaying Liu; Changjun Ding; Weixi Zhang; Yawei Wei; Yongbin Zhou; Wenxu Zhu (Journal of Soil Science and Plant Nutrition, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Valorization of the microalgae fixing CO2 from flue gas by co-hydrothermal liquefaction with high-protein microalgae: Denitrogenation of bio-oil by ash and high energy recovery - Huihui Liu; Youjian Zhu; Wei Yang; Yawei Li; Haiping Yang; Yingquan Chen; Xianhua Wang; Hanping Chen (Fuel, 2023)

Overview of the main biological mechanisms linked to changes in periodontal ligament stem cells and the inflammatory microenvironment - Xuetao Zhao; Hongbing Lin; Tong Ding; Yawei Wang; Na Liu; Yuqin Shen (Journal of Zhejiang University-SCIENCE B, 2023)

Exploring the mechanism of Chaihujia Longgu Muli decoction in the treatment of epilepsy in rats based on the RhoA/ROCK signaling pathway - Gang Feng; Xianghua Liu; Baoying Wang; Ruixing Li; Yaxin Chang; Nannan Guo; Yawei Li; Tiantian Chen; Bingxiang Ma (Molecular Biology Reports, 2023)

What Drives Migrants Back to Set up Firms? Return-home Entrepreneurial Intention of Rural Migrant Workers in China - Huasheng Zhu; Yawei Chen; Hua Zhang; Zhangfei Liu (Chinese Geographical Science, 2023)

Isomer-specific perfluoroalkyl acids accumulation, excretion and maternal transfer to eggs in chickens around a fluorochemical manufactory in China - Yan Gao; Boyu Song; Anen He; Chao Liu; Yao Lu; Juan Li; Jianjie Fu; Yong Liang; Yawei Wang (Science of The Total Environment, 2023)

Getting insight into the oxidation of SO2 to SO3 over P modified VW/Ti catalyst: Effect and inhibition mechanism - Zijun Yin; Yuxiu Zhong; Jingwen Lu; Tao Liu; Yawei Song; Mengxia Qing; Lele Wang; Yi Wang; Song Hu; Sheng Su; Jun Xiang (Chemical Engineering Journal, 2023)

Environmental characteristics and unified failure mode classification system for mining landslides in the karst mountainous areas of southwestern China - Zuliang Zhong; Yawei Xu; Nanyun Wang; Xinrong Liu; Guofu Gao (Carbonates and Evaporites, 2023)

Interfacial role of Ionic liquids in CO2 electrocatalytic Reduction: A mechanistic investigation - Shuai Guo; Yawei Liu; Yanlei Wang; Kun Dong; Xiangping Zhang; Suojiang Zhang (Chemical Engineering Journal, 2023)

Genotype by environment interactions in feed efficiency of Pacific abalone (Haliotis discus hannai) reared at different water temperatures - Wenchao Yu; Yawei Shen; Junyu Liu; Weiguang Zou; Zekun Huang; Miaoqin Huang; Ying Lu; Jinwei Ke; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture, 2023)

Effects of pH and incubation temperature on properties of konjac glucomannan and zein composites with or without freeze-thaw treatment - Rui Lai; Jie Liu; Yawei Liu (Food Hydrocolloids, 2023)

Radial and seasonal variation of sap flow and its response to meteorological factors in sandy Pinus sylvestris var. mongolica plantations in the Three North Shelterbelt of China - Yuqiang Tong; Jing Liu; Xu Han; Tong Zhang; Yinghao Dong; Mengge Wu; Shengjin Qin; Yawei Wei; Zhenju Chen; Yongbin Zhou (Agricultural and Forest Meteorology, 2023)

Multi-Tunnel Triboelectric Nanogenerator for Scavenging Mechanical Energy in Marine Floating Bodies - Ziyi Zhang; Zhiyuan Hu; Yan Wang; Yawei Wang; Qiqi Zhang; Dehua Liu; Hao Wang; Minyi Xu (Journal of Marine Science and Engineering, 2022)
The ocean has an abundant reserve of wave energy, which is considered to be a clean, widely distributed and inexhaustible resource. Triboelectric nanogenerators (TENGs) have been regarded as a reliable technology for harvesting wave energy due to its robustness and efficiency in scavenging random mechanical energy. In this study, a wave energy harvesting multi-tunnel TENG (MT-TENG) has been proposed, which could be integrated easily with ocean buoys. The MT-TENG consists of polytetrafluoroethylene (PTFE) balls and a multi-tunnel frame, which could convert wave energy into electrical energy. The multi-tunnel design also avoids possible mutual obstruction of the PFTE balls during the movement. Compared with the flat type structure, the multi-tunnel structure could enhance output performance obviously. With an agitation frequency of 2 Hz and vibration amplitude of 130 mm, the MT-TENG has a peak power density of 8.3 W/m3, which is five times that of the flat type structure TENG. By integrating with a life buoy and floating pipe line, the MT-TENG could harvest wave energy to light LEDs continuously, which could provide a new solution for maritime rescue and night offshore oil delivery warning.

Variations of human cerebral and ocular blood flow during exposure to multi-axial accelerations - Weipeng Li; Bitian Wang; Yawei Wang; Xiaoyu Liu; Wentao Feng; Tianya Liu; Zhujun Sun; Yu Liu; Songyang Liu; Yubo Fan (Medical & Biological Engineering & Computing, 2022)

The neonatal PROC gene rs1799809 polymorphism modifies the association between prenatal air pollutants exposure and PROC promoter methylation - Zhiyuan Li; Meng Yang; Leizhen Duan; Yongxiang Gong; Hongxia Xia; Francis-Kojo Afrim; Hui Huang; Xiaoxue Liu; Fangfang Yu; Yawei Zhang; Yue Ba; Guoyu Zhou (Environmental Science and Pollution Research, 2022)

Characterization of plant growth-promoting traits of Enterobacter sp. and its ability to promote cadmium/lead accumulation in Centella asiatica L. - Yi Li; Lijuan Mo; Xiaoqin Zhou; Yawei Yao; Jiangming Ma; Kehui Liu; Fangming Yu (Environmental Science and Pollution Research, 2022)

Manganese Accumulation and Plant Physiology Behaviour of Camellia oleifera in Response to Different Levels of Phosphate Fertilization - Fangming Yu; Meifen Xin; Yawei Yao; Xueru Wang; Kehui Liu; Yi Li (Journal of Soil Science and Plant Nutrition, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Enterobacter sp. FM-1 inoculation influenced heavy metal-induced oxidative stress in pakchoi (Brassica campestris L. ssp. Chinensis Makino) and water spinach (Ipomoea aquatic F.) cultivated in cadmium and lead co-contaminated soils - Fangming Yu; Yawei Yao; Jingpei Feng; Xueru Wang; Jiangming Ma; Kehui Liu; Yi Li (Plant and Soil, 2021)

Two-dimensional transition metal phthalocyanine sheet as a promising electrocatalyst for nitric oxide reduction: a first principle study - Shiqiang Liu; Yawei Liu; Zhiwen Cheng; Xiaoping Gao; Yujia Tan; Zhemin Shen; Tao Yuan (Environmental Science and Pollution Research, 2021)

Nitrification inhibitor DMPP offsets the increase in N2O emission induced by soil salinity - Yawei Li; Junzeng Xu; Xiaoyin Liu; Zhiming Qi; Haiyu Wang; Youjia Li; Linxian Liao (Biology and Fertility of Soils, 2020)

Neurobehavioral performance of PAH exposure in male coal miners in Shanxi, China: a cross-sectional study - Fang Wang; Liuye Yang; Bin Zhang; Gaisheng Liu; Chongjian Wang; Yawei Zhang; Tong Wang (International Archives of Occupational and Environmental Health, 2020)

Bioaugmentation-assisted phytoremediation of manganese and cadmium co-contaminated soil by Polygonaceae plants (Polygonum hydropiper L. and Polygonum lapathifolium L.) and Enterobacter sp. FM-1 - Yi Li; Jiamin Lin; Yuanyuan Huang; Yawei Yao; Xueru Wang; Chengzhao Liu; Ying Liang; Kehui Liu; Fangming Yu (Plant and Soil, 2020)

Population susceptibility differences and effects of air pollution on cardiovascular mortality: epidemiological evidence from a time-series study - Mengyao Liu; Xiaoxia Xue; Baosen Zhou; Yawei Zhang; Baijun Sun; Jianping Chen; Xuelian Li (Environmental Science and Pollution Research, 2019)

The adsorption behavior of multiple contaminants like heavy metal ions and p-nitrophenol on organic-modified montmorillonite - Yawei Liu; Jingde Luan; Chengyu Zhang; Xin Ke; Haijun Zhang (Environmental Science and Pollution Research, 2019)

Gene Cloning, Expression, and Antifungal Activities of Permatin from Naked Oat (Avena nuda) - Jian Liu; Deping Han; Yawei Shi (Probiotics and Antimicrobial Proteins, 2019)

Ammonia volatilization and nitrogen leaching following top-dressing of urea from water-saving irrigated rice field: impact of two-split surge irrigation - Junzeng Xu; Boyi Liu; Haiyu Wang; Wenhao Liu; Yawei Li; Yubin Dai; Tao Lu (Paddy and Water Environment, 2019)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Knockout of CTNNB1 by CRISPR-Cas9 technology inhibits cell proliferation through the Wnt/β-catenin signaling pathway - Lihong Guan; Shaoyi Zhu; Yawei Han; Ciqing Yang; Yanli Liu; Liang Qiao; Xiaoying Li; Han Li; Juntang Lin (Biotechnology Letters, 2018)

The differential expression of novel circular RNAs in an acute lung injury rat model caused by smoke inhalation - Zhiqiang Ye; Xuhui Liu; Yuewu Yang; Xianling Zhang; Ting Yu; Shigeng Li; Yawei Feng; Gangjian Luo (Journal of Physiology and Biochemistry, 2018)

Heavy-metal speciation redistribution in solid phase and potential environmental risk assessment during the conversion of MSW incineration fly ash into molten slag - Jingde Luan; Meiyun Chai; Yawei Liu; Xin Ke (Environmental Science and Pollution Research, 2018)

Does residual H2O2 result in inhibitory effect on enhanced anaerobic digestion of sludge pretreated by microwave-H2O2 pretreatment process? - Jibao Liu; Ruilai Jia; Yawei Wang; Yuansong Wei; Junya Zhang; Rui Wang; Xing Cai (Environmental Science and Pollution Research, 2017)

Metals compositions of indoor PM2.5, health risk assessment, and birth outcomes in Lanzhou, China - Yaqun Zhang; Suzhen Cao; Xiaoying Xu; Jie Qiu; Mingxia Chen; Dennis Wang; Donghong Guan; Chengyuan Wang; Xiao Wang; Bowen Dong; Huang Huang; Nan Zhao; et al. (Environmental Monitoring and Assessment, 2016)

Uncertainty analysis of SPI calculation and drought assessment based on the application of Bootstrap - Yi‐Ming Hu; Zhong‐Min Liang; Yong‐Wei Liu; Jun Wang; Lei Yao; Yawei Ning (International Journal of Climatology, 2015)
The Standardized Precipitation Index ( SPI ) has been widely used to monitor the drought status. In the estimation of SPI , an appropriate probability distribution function ( APDF ) is required to fit precipitation series with different timescales, such as 3‐month, 9‐month and so on. Then the standard normal distribution function is used to transform the cumulative probability derived from APDF to calculate the SPI value. Obviously, the estimation accuracy of SPI particularly depends on the sample that influences the selection of PDF and parameter estimation. However, the size of the observed sample is usually small, and it cannot perfectly present the statistical property of the population, which usually causes the uncertainty on calculation of SPI and in turn results in the uncertainty of drought assessment. Due to the existence of gap between the estimated SPI and the true SPI , when one obtains the estimation of SPI , it is necessary to know the reliability or uncertainty of the estimated SPI . In this article, a new method based on the Bootstrap method was put forward to analyse the impact of sampling uncertainty on the estimation of SPI and drought assessment. Through repeating samples from the original sample, a large number of Bootstrap samples are constructed, and based on each Bootstrap sample, the corresponding estimation of SPI for the given event can be obtained. Therefore, the sampling distribution of SPI for the given event can also be derived, on which both the point estimation and interval estimation of SPI for the given precipitation event can be provided, and the overall assessment of a drought event could be achieved. The case study shows that, compared with the original SPI calculation method, the proposed method not only provides equivalent assessment results, but also has the capability to assess the impact of sampling uncertainty on the uncertainty of SPI calculation and drought assessment.

Proteomic survey towards the tissue-specific proteins of mouse mitochondria - Yuan Wang; HaiDan Sun; YaWei Ru; SongYue Yin; Liang Yin; SiQi Liu (Science China Life Sciences, 2011)